Influencia de las características físico-químicas de aceites residuales de restaurantes en la calidad de biodiesel. - Álava Alchundia, Juan Andrés (2018)
In this study, the influence of the physical-chemical characteristics of waste oils from restaurants in Portoviejo city on the quality of biodiesel was evaluated. Previously, to characterize the residual oils, 57 restaurants derived from the sample size, zoned in the urban area, were surveyed. Obtaining palm oil as the main resource used for cooking food, estimating a residual oil generation of approximately 656l / week. A sample of residual oil was collected per restaurant to obtain a composite sample to which a pretreatment was carried out with a medium zeolite and sand filter, which allowed to reduce impurities in the oil. Physico-chemical analyzes determined that the residual oil possesses 0.42% acidity, a saponification index of 168mg / g, peroxide value 0.48mEqO2 / kg, melting point 25ºC, and humidity 0.17 %. To determine the quality of biodiesel, the NTE INEN 2482: 09 standard was used, obtaining as a result: sulfur content 0.03 Mg / kg, corrosion copper foil 1B, acid number 0.296 Mg KOH / g, being within the ranges of the norm, on the contrary, water and sediment 0.30%, kinematic viscosity 17.23 mm2 / s, density 911.4 Kg / m3, ash 0.57% and residual coal 0.55% surpass the ranges; giving it a regular quality, determining that the values of acidity and humidity of the residual oil influenced the quality of the biodiesel. A unit price analysis was applied to estimate the production cost of biodiesel from waste oils resulting in $ 5.51 per gallon.